A Boy's Ride - Zollinger, Gulielma, 1856-1917 (Salt Lake City, UT : Project Gutenberg, 2005)
"A Boy's Ride" by Gulielma Zollinger is a historical novel written in the early 20th century. Set in 1209 England, the narrative follows the adventures of a fourteen-year-old boy named Hugo Aungerville as he embarks on a quest to become a knight, caught against the backdrop of political intrigue and danger surrounding King John$1 (Bs oppressive rule. The story unfolds with Hugo$1 (Bs escape from his uncle$1 (Bs priory, the tragic fate of many noble children during this tumultuous time, and the imminent threats posed by the king$1 (Bs men as he navigates the perilous landscape. At the start of the novel, Hugo is introduced as a resourceful and brave boy who, against all odds, seeks to carve out his own fate. He rides through the English countryside with his deerhound, Fleetfoot, when he unexpectedly finds himself pursued by arrows shot from the woods, prompting him to seek refuge at the castle of the De Aldithelys. There, he encounters Josceline, the young lord of the castle, and learns of the treachery surrounding King John. This inciting incident sets the stage for Hugo to assume Josceline's identity, thereby allowing him the opportunity to assist in thwarting the king's dangerous plans. As the narrative progresses, various characters, including the loyal but superstitious servant Humphrey and the cunning spy Walter Skinner, are introduced, hinting at the intricate layers of loyalty, deception, and bravery that will play a critical role in Hugo$1 (Bs journey. (This is an automatically generated summary.)s
Release date is 2005-03-01
Produced by Patricia L. Ehler, Suzanne L. Shell, Charles Franks and the Online Distributed Proofreading Team
Keywords: Great Britain -- History -- Medieval period, 1066-1485 -- Juvenile fiction